A Case of Low-Grade Oncocytic Tumor/Chromophobe Renal Cell Carcinoma (Oncocytic Variant) of the Kidney - Noriyoshi Ishikawa; Nao Kimura; Toshio Yoshida; Ichiro Yoshimura; Ken Nakahara; Toyonori Tsuzuki; Osamu Tokunaga (Case Reports in Pathology)
The oncocytic variant of chromophobe renal cell carcinoma (oChRCC) and low-grade oncocytic tumor (LOT) is introduced as new renal disease entity. Both of these tumors are low-grade malignancies consisting of cells with eosinophilic cytoplasm. Distinguishing between eosinophilic variant of chromophobe renal cell carcinoma (eCRCC) and oncocytoma is often a diagnostic challenge in routine surgical pathology. However, oChRCC and LOT might be independent disease entities that might not fit completely into any of these categories. Histologically, these tumors have greater morphological similarity with oncocytoma than with ChRCC. However, immunohistochemically, they exhibit diffuse and dense positivity for CK7 and are negative for CD117. In the present case, we initially had difficulty distinguishing among oncocytoma, eCRCC, and type 2 papillary renal cell carcinoma (2-pRCC). However, after learning about new disease entities such as oChRCC and LOT, we were able to diagnose this tumor.